Effect of sulfur on the ion concentration of pore solution and the hydration of calcium aluminate cement. (September 2015) - Zhang, Yefan; Li, Nan; Yan, Wen
Abstract: The ion concentration, PH value of pore solution and the hydration of two low iron calcium aluminate cements based on bauxite (BCACs) with different sulfur content were investigated by XRD, ICP-OES, PH meter and SEM. The results indicate that the sulfur in the bauxite and coal results in the formation of ye'elimite (C4 A3 Š) in BCAC. The more the sulfur content in BCAC the more the C4 A3 Š formed. The hydration of C4 A3 Š decreases the ion concentrations of Ca, Al and the PH values but increases the concentration of S. Hydration and hydrates of CA are influenced by the hydration of C4 A3 Š in BCAC. CAH10 is found in the hydration of both BCAC samples, but C2 AH8 is only found in the hydrates of the BCAC with lower SO3 content.